2011
DOI: 10.5194/acp-11-10193-2011
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: On the effect of water-soluble compounds removal on EC quantification by TOT analysis in urban aerosol samples

Abstract: Abstract. In this work, three different thermal protocols were tested on untreated and water-washed aerosol samples to study the influence of soluble organic and inorganic compounds on EC measurements. Moreover, analyses on the water soluble extracts were carried out. The aim was to find out the most suitable protocol to analyse samples collected in a heavily polluted area. Indeed, the tests were performed on real samples collected at an urban background station in the Po Valley, which is one of the main pollu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
54
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 35 publications
9
54
2
Order By: Relevance
“…The removal of water-soluble organic compounds from the filter by washing procedures significantly reduces pyrolysis during the thermal analysis (Piazzalunga et al, 2011). Furthermore, the washing procedure also removes other soluble components in the sample (i.e.…”
Section: Measurements Of Ec and Ocmentioning
confidence: 99%
See 3 more Smart Citations
“…The removal of water-soluble organic compounds from the filter by washing procedures significantly reduces pyrolysis during the thermal analysis (Piazzalunga et al, 2011). Furthermore, the washing procedure also removes other soluble components in the sample (i.e.…”
Section: Measurements Of Ec and Ocmentioning
confidence: 99%
“…Intercomparisons between the TOA methods have shown that the temperature protocol and the optical detection technique (transmission versus reflection) can make a significant difference in the measured EC content Schmid et al, 2001;Schauer et al, 2003;Subramanian et al, 2006;Cavalli et al, 2010;Piazzalunga et al, 2011). Determining the temperature at which all OC and no EC evolves in He, air or O 2 is challenging.…”
Section: Measurements Of Ec and Ocmentioning
confidence: 99%
See 2 more Smart Citations
“…Propata samples were analyzed following the EUSAAR_2 protocol [49], while a NIOSH-like protocol (He_870) [50] has been used in the case of the Milan samples. This choice has been taken to have continuity with previous respective measurement campaigns.…”
Section: Chemical Characterizationmentioning
confidence: 99%